EDUCATIONAL MANAGEMENT MODEL OF A BUDDHIST SUNDAY CENTER - Tewasirinako (Lakaluk), Phra Watchara; ., Phrakruphromkhetkanarak; Hemrangsee, Jaruayporn (Journal of Social Science and Cultural, 2020)
Educational management Is the key to driving education By relying on process skills that interact between teachers and learners Students to learners Learners and the Environment And teachers and the environment If there is a good interaction between each other Inevitably leads to better learning efficiency Therefore, learning management is an important part of enhancing the effectiveness and efficiency of learners. Starting from planning Course management Teaching and learning management, evaluation and evaluation of learning The authors studied from the monks’ teaching and learning in the Sunday Buddhist Study Center, where education was considered as an important principle in driving education. Through relational process skills There are four aspects of the relationship building process: 1) between teachers and learners 2) learners and learners 3) learners and environment 4) teachers and environment If there are 4 good interactions Indeed, the learning is good and effective in the learner, and the teacher who is the monk is able to teach the principles or content of teaching effectively. After teaching and teaching To develop and improve In the teaching and learning of the Sunday Buddhist Study Center It is considered an organization that has received cooperation from Palang Bowon (Ban, Temple, School). It is a learning management by using the temple as an educational center with monks and volunteers who have cooperated to help teach. Give knowledge and understanding to the youth Therefore, correct learning management is required Together with a learning plan And youth evaluation and evaluation Efficiency and effectiveness